Genetic variants in Barrett's esophagus and esophageal adenocarcinoma: a literature review. Issue 8 (19th March 2019) - Callahan, Zachary M; Shi, Zhuqing; Su, Bailey; Xu, Jianfeng; Ujiki, Michael
SUMMARY: Surveillance of Barrett's esophagus (BE) is a clinical challenge; metaplasia of the distal esophagus increases a patient's risk of esophageal adenocarcinoma (EAC) significantly but the actual percentage of patients who progress is low. The current screening recommendations require frequent endoscopy and biopsy, which has inherent risk, high cost, and operator variation. Identifying BE patients genetically who are at high risk of progressing could deemphasize the role of endoscopic screening and create an opportunity for early therapeutic intervention. Genetic alterations in germline DNA have been identified in other disease processes and allow for early intervention or surveillance well before disease develops. The genetic component of BE remains mostly unknown and only a few genome-wide association studies exist on this topic. This review summarizes the current literature available that examines genetic alterations in BE and EAC with a particular emphasis on clinical implications.